(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: Oral Cancer Is One Of The World's Most Common Types Of Cancer, With Delayed Diagnosis And Poor Prognosis. IndiaIs Among The Leading Countries With A High Rate Of Oral Cancer Due To Its Increased Tobacco Use Rate.Aim: This Study Aims To Assess The Prevalence Of Oral Cancer Among Tobacco And Non-Tobacco Users In Tamil Nadu.Materials And Method: A Systematic Review Of Cross-Sectional Studies Were Performed. The Data Was Searched Using ElectronicDatabases, And 376 Articles Were Screened. The Intervention And Outcomes Were Assessed In The Studies Included In TheSystematic Review. The Bias Assessment Done For The Article Was Based On The Newcastle-Ottawa Scale.Results: Overall Analysis Of The Studies Shows That The Prevalence Of Oral Cancer In Tamil Nadu Has Been Significantly IncreasingAnd That Smokeless Tobacco Causes Oral Cancer Compared With Other Forms Of Tobacco.Conclusion: The Prevalence Of Oral Cancer In Tamil Nadu Is Increasing Significantly With The Usage Of The Increased Amount OfTobacco, And Awareness Of The Ill Effects Of Tobacco Usage May Considerably Decrease The Rates.